Antimicrobial activity of fungi isolated from Tan Dao mangrove forest in Khanh Hoa - Duy Ngoc, Ngo Thi; Hoai Trinh, Phan Thi; Thanh Van, Tran Thi; Pivkin, Mikhail V.; Yurchenko, Anton N.; Thuy Hang, Cao Thi; Dieu Trang, Vo Thi; Dinh Hung, Le; Nhu Khanh, Huynh Hoang; Duc Thinh, Pham (Academia Journal of Biology, 2022)
Mangrove-derived fungi are the potential source of novel metabolites, comprising unique molecular structures with diverse bioactivities. In this study, 32 fungal strains isolated from the Tan Dao mangrove forest in Khanh Hoa province were investigated for their ability to produce antimicrobial agents using the disc diffusion method. Seventy-eight percent of obtained fungi (25 out of 32 isolates) exhibited antimicrobial activity against at least two test pathogens. Of them, bacteria Bacillus cereus and Streptococcus faecalis were the most susceptive to the antimicrobial activity of all fungal isolates with inhibition zones ranging from 8 to 36 mm, respectively, followed by Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, and Pseudomonas aeruginosa. There were only three fungal isolates that showed antimicrobial activity towards Candida albicans with the inhibition zone of 8−17 mm diameter. The strain LM.8.1 showing significant activity against all test microorganisms was identified as Penicillium sp. LM.8.1. The effect of culture conditions including pH, salinity, and incubation time on the production of antibacterial compounds of fungus Penicillium sp. LM.8.1 was also studied. The results indicated that fungi isolated from the Tan Dao mangrove forest possess potent antimicrobial properties and should be further investigated.